A Sistematic Literature Review : Implementasi Asesmen Diagnostik pada Kurikulum Merdeka - Nugroho, Dennis; Wirawan, Wirawan; Febriantania, Putri; Ridaningsih, Ida (Jurnal Pendidikan Islam, 2023)
This research aims to examine scientific articles that are relevant and related to the implementation of diagnostic assessments. The research method used in writing this article is a literature review. The literature review was obtained from articles published in the last 5 years, namely from 2019 to 2023. The literature search was focused on the keyword "Diagnostic Assessment" so that a total of 29 articles were obtained, for research at the secondary school level, which were accessed via the Publish or Peerish application. However, after going through the screening stage there were 17 articles in the open access category and relevant to the topic of discussion. Based on the results of the literature review analysis, there are doubts from teachers to carry out diagnostic assessments because teachers have not received a lack of socialization regarding the Implementation of the Independent Curriculum (IKM), so that training and guidance for teachers needs to be carried out. Apart from that, in the implementation of diagnostic assessments, it was found that (1) diagnostic assessments can be implemented in the independent curriculum at primary and secondary school levels, (2) implementation of diagnostic assessments can also help students overcome learning problems with various learning styles. (3) Diagnostic assessments can evaluate students' strengths and weaknesses (4) while from the educator/teacher side they can be used to plan learning strategies. Apart from that, there are also diagnostic assessment tools that teachers can use, such as the Fout-tier Test Diagnostic and Google Form.